Effect of Copper on Hydrogenotrophic Denitrification: A Review - Gaire, Parash; Maharjan, Rabin (International Journal on Engineering Technology and Infrastructure Development, 2025)
Nitrate contamination of water sources is a significant issue that impacts human health and the environment. This review explores the role of copper in the hydrogenotrophic denitrification (HD) process, focusing on how copper influences denitrification enzymes and microbial activity. Copper plays a critical role in activating nitrous oxide reductase, an enzyme responsible for the final step of denitrification. An imbalance in copper availability either deficiency or excess can lead to incomplete nitrate conversion and elevated nitrous oxide (N₂O) emissions. This study delves into the causes and effects of nitrate pollution, the mechanisms underlying hydrogenotrophic denitrification, and the impact of copper on these processes. Its findings underscore the importance of understanding the optimal copper concentrations to enhance nitrate removal and reduce N2O emissions.